2021
DOI: 10.1038/s41467-021-26041-0
|View full text |Cite
|
Sign up to set email alerts
|

Human commensal gut Proteobacteria withstand type VI secretion attacks through immunity protein-independent mechanisms

Abstract: While the major virulence factors for Vibrio cholerae, the cause of the devastating diarrheal disease cholera, have been extensively studied, the initial intestinal colonization of the bacterium is not well understood because non-human adult animals are refractory to its colonization. Recent studies suggest the involvement of an interbacterial killing device known as the type VI secretion system (T6SS). Here, we tested the T6SS-dependent interaction of V. cholerae with a selection of human gut commensal isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 80 publications
(133 reference statements)
0
37
0
Order By: Relevance
“…We would expect similar trends, namely, the emergence of HMV in capsulated populations, as the adaptive response is very conserved across the diverse panel of environments tested. Further, it has been shown that the capsule provides competitive advantages during direct competition 16 , 17 and the costs associated with some traits, like HMV, could be offset by the benefits it provides in a mixed community. Also, similar wzc hypermucoid mutants isolated in vivo were shown to mediate phagocytosis resistance and increase dissemination in murine models 62 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We would expect similar trends, namely, the emergence of HMV in capsulated populations, as the adaptive response is very conserved across the diverse panel of environments tested. Further, it has been shown that the capsule provides competitive advantages during direct competition 16 , 17 and the costs associated with some traits, like HMV, could be offset by the benefits it provides in a mixed community. Also, similar wzc hypermucoid mutants isolated in vivo were shown to mediate phagocytosis resistance and increase dissemination in murine models 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The Klebsiella capsule increases cellular survival under stress or biotic aggressions from other bacteria 17 or the host immune system [54][55][56] . Yet, there is a lack of studies comprehensively addressing how a major virulence factor such as the capsule, which is widespread across clades, affects adaptation to novel environments at the microevolutionary level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the limited data in the immune protein database, no immune proteins were identified around other predicted effector proteins. Bacteria can also withstand T6SS attacks through immunity protein-independent mechanisms ( Flaugnatti et al, 2021 ). A previous study reported that T6SS orphan immunity gene clusters were present in the human gut microbiome and suggested that the acquisition and maintenance of orphan immune genes were a common mechanism for Bacteroidetes to resist bacterial antagonism in the human gut microbiome ( Ross et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the benefits supplied by probiotic organisms are: 1) improvement of the intestinal epithelial layer barrier through secretion of metabolites and small molecules, 2) secretion of antimicrobial and anti-inflammatory factors, 3) ability to enhance innate immunity and modulate pathogen-induced inflammation. 4) competition with opportunistic pathogens for space and nutrients, and 5) inhibition of pathogen adhesion and translocation ( Zhang et al, 2017 ; Wan et al, 2019 ; Flaugnatti et al, 2021 ) ( Figure 2 ). However, these native abilities can be overwhelmed in response to dietary changes, stress, broad spectrum antibiotic treatments or other causes of dysbiosis ( Gagliardi et al, 2018 ).…”
Section: Synthetic Biology Approaches To Antimicrobial Drug Resistancementioning
confidence: 99%